Description and evaluation of the Community Ice Sheet Model (CISM) v2.1 - Lipscomb, William H. (author); Price, Stephen F. (author); Hoffman, Matthew J. (author); Leguy, Gunter R. (author); Bennett, Andrew R. (author); Bradley, S.L. (author); Evans, Katherine J. (author); Fyke, Jeremy G. (author); Kennedy, Joseph H. (author) (Geoscientific Model Development, 2019)
We describe and evaluate version 2.1 of the Community Ice Sheet Model (CISM). CISM is a parallel, 3-D thermomechanical model, written mainly in Fortran, that solves equations for the momentum balance and the thickness and temperature evolution of ice sheets. CISM's velocity solver incorporates a hierarchy of Stokes flow approximations, including shallow-shelf, depth-integrated higher order, and 3-D higher order. CISM also includes a suite of test cases, links to third-party solver libraries, and parameterizations of physical processes such as basal sliding, iceberg calving, and sub-ice-shelf melting. The model has been verified for standard test problems, including the Ice Sheet Model Intercomparison Project for Higher-Order Models (ISMIP-HOM) experiments, and has participated in the initMIP-Greenland initialization experiment. In multimillennial simulations with modern climate forcing on a 4 km grid, CISM reaches a steady state that is broadly consistent with observed flow patterns of the Greenland ice sheet. CISM has been integrated into version 2.0 of the Community Earth System Model, where it is being used for Greenland simulations under past, present, and future climates. The code is open-source with extensive documentation and remains under active development. Physical and Space Geodesy